Autoethnography as a Qualitative Methodology: Conceptual Foundations, Techniques, Benefits and Limitations - Kudzayi Savious Tarisayi (University of Bologna, 2023)
This paper provides an overview of autoethnography as a qualitative research methodology. It outlines the conceptual underpinnings, evolution, key features, data collection methods, and theoretical orientations that have shaped autoethnography. The unique affordances of autoethnography are discussed, including producing thick insider descriptions, illuminating hidden social worlds, disrupting problematic research power hierarchies, enhancing researcher reflexivity, and increasing accessibility through evocative storytelling. Critiques and limitations of the method are also examined, including issues of ethics, rigor, generalizability, and tendencies toward self-indulgence. The paper advocates for incorporating autoethnography into research contexts to harness its strengths for generating nuanced, embodied accounts of cultural experience, although careful implementation is required. Overall, the examination delineates how autoethnography offers profound subjective, yet systematic means for inquiry aimed at furthering human self-understanding and sociocultural critique.